Pengelolaan Wilayah Pesisir Dalam Tanggungjawab Masyarakat Adat - Piris, Hendry John (Jurnal Saniri, 2023)
The potential for natural resources in coastal areas is very abundant starting from the coast, plains, affecting the lives of coastal communities. Of course, the synergy of nature and arts and culture is closely related to the social and economic life of the local community. Efforts to maintain the harmonization of nature and cultural arts of coastal communities.The research method in this writing uses the type of normative juridical research, which is carried out based on the main legal material by examining the theories, concepts, legal principles and laws and regulations related to this research. The procedure for collecting legal materials uses library research, the library as a means to obtain primary legal materials and secondary legal materials, then the legal materials are collected and analyzed. Legal material analysis techniques in this study used descriptive analysis techniques.The state and the rules have guaranteed indigenous peoples to their natural environment to ensure the sustainability of the environment from generation to generation, without any prohibitions for people to use the environment as a source of livelihood. The wisdom of indigenous peoples with customs that have been formed and intertwined from generation to generation will guarantee the preservation of the environment and territory as a priority place and a necessity of life. The existence and role of indigenous peoples in efforts to protect and manage the environment will have an impact on the indigenous peoples themselves and the protection of their territories.